Process of Democratization, Dynastic Politics And Intra-Party Democracy In Pakistan - Dr. Rashid Aftab; Dr. Sartaj; Mr. Kashif Zaheer; Mr. Zesshan Khan; Asma Hussain (Al-Qanṭara, 2025)
Dynastic politics has remained one of the major themes in politics and governance across the globe. Like other transitional democracies, Pakistan faces multiple challenges. Dynastic politics is one of the major hurdles that directly and indirectly affects the process of democratization in the country. Political parties in Pakistan are greatly influenced and shaped by dynastic politics, with party heads or a few individuals dominating the decision-making processes related to party objectives, candidate selection, and alliances with other political parties. Regardless of their ideological orientation or organizational form, most political parties are heavily shaped by dynastic politics. This research article analyzes the impact of dynastic politics and highly centralized party structures on the process of democratization in Pakistan.